In situ ultrafast separation and purification of oil/water emulsions by superwetting TiO2 nanocluster-based mesh. Issue 16 (13th April 2016) - Lin, Xin; Chen, Yuning; Liu, Na; Cao, Yingze; Xu, Liangxin; Zhang, Weifeng; Feng, Lin
Abstract : In situ emulsions separation and purification were realized by a TiO2 nanocluster-based mesh in an ultrafast and efficient way. Abstract : Combined with special wettability and photocatalytic properties, a TiO2 nanocluster-based mesh was constructed, successfully used for emulsion separation and soluble contaminants degradation under UV illumination in one step, with extremely high flux and efficiency. This work provides a new way to develop multifunctional materials for potential use in water remediation.